2013
DOI: 10.3324/haematol.2013.083972
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells from patients with myelodyplastic syndrome display distinct functional alterations that are modulated by lenalidomide

Abstract: ABSTRACTtypes including MDS associated with single del(5q), and characterized their clonogenicity and differentiation potential. Methods Human samplesTwenty MDS patients were studied; their characteristics are detailed in Online Supplementary Table S1. Our control cohort consisted of one male and five female healthy individuals undergoing orthopedic surgery with a median age of 60 years (range, 56-65). MSC were obtained as previously described. 18 Patients were classified for the study as "lower risk" with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 55 publications
5
93
0
Order By: Relevance
“…31,32 Just as predicted, most of the cultured and primary MDS-MSC were larger and irregular and expressed significantly higher amounts of SA-β-gal and the senescence-related molecule, p21. These findings are similar to those of previous studies, 10,14 but the investigators of those studies did not provide a detailed analysis of the different MDS subsets and the functional changes related to senescence in MDS pathology. In our study, not all of the cases exhibited an increase in senescence (22/32, 68.7%).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…31,32 Just as predicted, most of the cultured and primary MDS-MSC were larger and irregular and expressed significantly higher amounts of SA-β-gal and the senescence-related molecule, p21. These findings are similar to those of previous studies, 10,14 but the investigators of those studies did not provide a detailed analysis of the different MDS subsets and the functional changes related to senescence in MDS pathology. In our study, not all of the cases exhibited an increase in senescence (22/32, 68.7%).…”
Section: Discussionsupporting
confidence: 88%
“…In keeping with our findings, some studies demonstrated that MDS-MSC displayed insufficient hematopoietic support capability compared with normal controls. 10,13,14 However, other reports suggested that MDS-MSC may have normal support capacity. 11,12,34 The discrepancies in these results might be attributed to differences between patients, cellular populations and experimental protocols in the various studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such proliferation defects have also been described in MSCs from several other hematopoietic disorders, such as acute lymphoblastic leukemia (ALL) [31,32], chronic lymphocytic leukemia (CLL) [33,34], and especially MDS [16,17,35,36]. A slight decrease of their clonogenic potential (CFU-F) was also observed that was inversely correlated with the PDT values.…”
Section: Discussionmentioning
confidence: 72%
“…However, it is not yet evident if MSC long-term hematopoietic-supporting activity in AML at diagnosis is intrinsically impaired [12] or not [10]. Otherwise, several recent reports have highlighted the abnormal MSC function in chronic preleukemic diseases such as myelodysplastic syndromes (MDSs) [15][16][17] in contrast to chronic myelogenous leukemia (CML) [18,19].…”
mentioning
confidence: 99%